ABSORPTIVE CAPACITY AND INNOVATION CAPABILITY: ASSESSING THE IMPACT ON SMES PERFORMANCE IN THE NEW NORMAL ERA - Prakasa, Yudha; Sujoko, Anang; Aziz, Nana Abdul; Muttaqin, Andhyka (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
The new normal era during the COVID-19 pandemic has presented opportunities and challenges for SMEs. This study aimed to determine the effects of absorptive capacity and innovation capability on business performance. The research involved 189 creative SMEs owners in Malang City. The sampling technique uses proportional random sampling. Data were collected by distributing questionnaires to respondents. The data analysis used partial least squares using high-order construction. The results showed that absorptive capacity significantly affects business performance, and absorptive capacity significantly affects innovation capability. However, innovation capability had no significant effect on business performance. Innovation capability has also not been proven to influence Absorptive Capacity and Business Performance indirectly. The practical implication is that SMEs owners should develop the absorptive capacity to reach, assimilate, and acquire new knowledge to achieve better SMEs performance. Simultaneously, innovation capability does not automatically improve SMEs' performance. SMEs need extra effort to produce innovations that are rare, unique, and difficult to imitate to survive the new normal era.  JEL : D81, M13, O31.ABSTRAKEra new normal di masa pandemi COVID-19 menghadirkan peluang dan tantangan bagi UMKM. Penelitian ini bertujuan untuk menguji pengaruh absorptive capacity dan innovation capability terhadap business performance. Penelitian ini melibatkan 189 pemilik UMKM kreatif di Kota Malang. Teknik pengambilan sampel menggunakan proportional random sampling. Pengumpulan data dilakukan dengan menyebarkan kuesioner kepada responden. Analisis data menggunakan partial least squares using high-order construction. Hasil penelitian menunjukkan bahwa absorptive capacity berpengaruh signifikan terhadap business performance, dan business performance berpengaruh signifikan terhadap innovation capability. Namun, innovation capability tidak berpengaruh signifikan terhadap business performance. Innovation capability juga belum terbukti mempengaruhi absorptive capacity dan business performance secara tidak langsung. Implikasi praktisnya, pemilik UMKM harus mengembangkan absorptive capacity untuk menjangkau, mengasimilasi, dan memperoleh pengetahuan baru untuk mencapai kinerja UMKM yang lebih baik. Secara bersamaan, innovation capability tidak secara otomatis meningkatkan kinerja UMKM. UMKM membutuhkan upaya ekstra untuk menghasilkan inovasi yang langka, unik, dan sulit ditiru untuk bertahan di era normal yang baru.Kata Kunci : absorptive capacity, innovation capability, business performance, SMEs, new normal.